Earthquake Risk Assessment – Effect of a Seismic Event in a Moderate Seismic Area - Kegyes-Brassai, O. K.; Ray, R. P. (Acta Technica Jaurinensis, 2015)
This paper presents the process of earthquake risk analysis from the probabilistic determination of seismic hazard and local site effects, through the evaluation of building vulnerability to an event resulting in seismic risk maps. These results can then serve as useful tools for decision makers and insurance companies, and can be applied directly to overall risk management plans of cities. Finally a case study for seismic risk assessment performed in city of Győr is presented, taking into account local site effects based on response analysis with more than 6000 realizations and rapid visual screening of 5000 building to obtain the seismic risk.